The Scale of Public Space: Taksim Square in Istanbul - Senem Zeybekoglu Sadri (Journal of Contemporary Urban Affairs, 2017)
This article aims at following the traces of the transformation of public sphere in Turkey through its manifestations on urban public spaces with the case study of Taksim Square. In this attempt, the article illustrates how Taksim square, as a public space, has been shaped by struggles between different ideologies, discourses, political decisions and daily activities taking place at personal, interpersonal, local, national, supranational and global scales. Through this way this article also aims at understanding how these contestations at different scales are affecting people, individually and collectively, from daily life practices to political integration. The article also discusses that our daily life practices and preferences are political decisions and our participation in public sphere occurs through those daily actions of the personal spheres. Therefore, the article suggests that a paradigm shift is needed in the design and production of the built environments that will facilitate the coexistence of multiple counter publics. Copyright © 2017 Journal of Contemporary Urban Affairs.